PENGARUH BUDAYA ORGANISASI, KOMPENSASI, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA PALU - Putranto, Bayu Reza Hadi; Natsir, Syahir; Miru, Sulaeman (Katalogis, 2018)
The study intends to determine and analyze simultaneous and partial influence of organizational culture, compensation, and motivation on performance of officials at Pratama Tax Office Palu. Primary data is gathered from questionnaires distributed to 114 respondents at the Pratama Tax Office of Palu. Method of analysis is multiple linear regressions. The result concludes that 1) organizational culture, compensation, and motivation simultaneously have positive and significant influence on performance of officials at Pratama Tax Office Palu; 2) organizational culture partially has positive and significant influence on performance of officials at Pratama Tax Office Palu; 3) compensation partially has positive and significant influence on performance of officials at Pratama Tax Office Palu; 4) motivation partially has positive and significant influence on performance of officials at Pratama Tax Office Palu. The result of the regression test indicates an Adjusted R- Square of 0.490, which means that 49% of work performance at Pratama Tax Office Palu is influenced by organizational culture, compensation, and motivation; the remining is influenced by variables that are not studied.